Three Cycles of Radiofrequency Ablation Are More Efficacious Than Two in the Management of Morton's Neuroma. Issue 2 (April 2018) - Brooks, David; Parr, Adam; Bryceson, William
Background . Morton's neuroma is a common cause of forefoot pain. Outcomes of conservative therapy are mixed and many patients undergo operative intervention. Radiofrequency ablation has recently gained favor as a treatment option, although the optimal regime is unknown. This study investigates the effectiveness of 2 versus 3 cycles of radiofrequency ablation for the treatment of Morton's neuroma. Methods . We surveyed a cohort of patients with Morton's neuroma who had progressed to radiofrequency ablation after failed conservative treatment. Patients received either 2 or 3 cycles of radiofrequency ablation by a single surgeon. We assessed patients based on their change in numerical pain rating scale, symptom improvement, complications, and progression to surgical excision through a series of telephone interviews. Outcomes between the 2 treatment arms were compared by parametric tests. Results . Twenty-eight patients were included in the study. Eighteen patients with 21 neuromas received 2 cycles and 10 patients with 11 neuromas received 3 cycles. Mean time of follow-up was 12.9 months. Overall, 88% of patients were either very or moderately satisfied with their outcome. In patients who received 2 cycles mean numerical pain scores decreased from 7.9 ± 1.1 to 3.4 ± 2.4 postprocedure. Three patients progressed to operative excision. In patients who received 3 cycles, numerical pain scores decreased from 8.0 ± 1.0 to 1.5 ± 2.0 postprocedure. One patient progressed to operative excision. Patients who received 3 cycles had reduced medium-term pain postoperatively compared with 2 cycles (3.4 ± 2.4 vs 1.5 ± 2.0, P = .011). Conclusion . Radiofrequency ablation provides a high rate of patient satisfaction in the treatment of Morton's neuroma with few side effects. It appears that 3 cycles may be superior to 2 cycles but a randomized controlled trial will be required to confirm these results. Levels of Evidence: Intervention, Level III: Comparative study without concurrent controls